Perancangan E-Commerce pada UMKM Rumahan Berbasis Platform Openchart Untuk Meningkatkan Daya Saing Digital di Kecamatan Sungai Aur - Fitri, Annisa; Annas, Firdaus; Ayu Maydani Hsb, Alisya (Yayasan Lembaga Studi Makwa, 2023)
Digitalization is one of the important factors and has become a primary need in improving the competitiveness of micro, small and medium enterprises (MSMEs), especially in the era of technology-based economic transformation. However, many home-based MSMEs in Sungai Aur sub-district still face challenges in adopting e-commerce technology, such as lack of technical understanding, limited resources and lack of access to affordable technology solutions and access to relevant solutions. This research aims to design an open source-based platform using openchart, tailored to the local needs of MSMEs, to improve their digital competitiveness and adapt to the changing modern business landscape and expand their market reach. This research uses a Research and Development (R&D) method that involves a needs analysis. The needs analysis was conducted through interviews with home-based MSME players in Sungai Aur sub-district to identify and understand their constraints and specific expectations and needs. Next, a prototype e-commerce platform was designed using a user-centered design approach to ensure ease of use and relevance of features. The results and research show that the designed openchart-based platform is able to meet the needs of MSMEs in product management, transactions and digital marketing, and also this platform improves the operational efficiency of MSMEs and expands their market reach. Findings. The findings of this research are that the development of an openchart-based e-commerce platform using the R&D method can be an effective solution in helping home-based MSMEs in Sungai Aur sub-district transform towards digital, while strengthening their competitiveness in the wider market.